2012
DOI: 10.1111/j.1748-1716.2012.02436.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal cortical and medullary blood flow during modest saline loading in humans

Abstract: In normal humans, changes in RMBF are not necessarily involved in the natriuretic response to modest saline loading. This result is in line with data from conscious rodents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 75 publications
2
19
0
Order By: Relevance
“…108,109 Thus, changes in body fluid volume status should affect the determinants of kidney tissue PO 2 , but the overall effect on kidney oxygenation will depend on the balance of effects on kidney oxygen delivery and consumption, which cannot necessarily be predicted from first principles. For example, extracellular fluid volume expansion (saline loading) can, 110 although perhaps not always, 111,112 lead to increased RBF and medullary perfusion and so increased oxygen delivery. It also inhibits tubular sodium reabsorption and so decreases oxygen consumption.…”
Section: Contrast-induced Nephropathymentioning
confidence: 99%
“…108,109 Thus, changes in body fluid volume status should affect the determinants of kidney tissue PO 2 , but the overall effect on kidney oxygenation will depend on the balance of effects on kidney oxygen delivery and consumption, which cannot necessarily be predicted from first principles. For example, extracellular fluid volume expansion (saline loading) can, 110 although perhaps not always, 111,112 lead to increased RBF and medullary perfusion and so increased oxygen delivery. It also inhibits tubular sodium reabsorption and so decreases oxygen consumption.…”
Section: Contrast-induced Nephropathymentioning
confidence: 99%
“…It requires a comprehensive approach using multi‐faceted measuring modalities including non‐invasive imaging such as ultrasound, computer tomography and magnetic resonance imaging (Damkjaer et al . , Pohlmann et al . , Brabrand et al .…”
mentioning
confidence: 99%
“…It was suggested that increased oxidative stress in the renal medulla decreases medullary perfusion and thereby increases sodium reabsorption during hypertension . We have adapted imaging technology to quantify regional renal blood flows in man allowing imaging procedures to be added to measurements of haemodynamic, hormonal and renal responses to volume expansion. For the present study, we hypothesized that in patients with mild essential hypertension, but no measurable target organ damage, the response of local renal flow to saline loading differs from baseline and from the response of normotensive subjects.…”
Section: Introductionmentioning
confidence: 99%